Pavel Kukolnik and the Polish-Speaking Poets of Lithuania - Лавринец, Павел (Slavistica Vilnensis, 2018)
[full article, abstract in Russian; abstract in Lithuanian and English]Relations between the Vilnius censor, historian and poet Pavel Kukolnik (1795–1884) and the Polish-speaking poets of Lithuania were considered in the biographical and scientific literature, but the topic was not exhausted. The rapprochement between Kukolnik and some historians and writers of Vilnius (Adam Honory Kirkor, Teodor Narbutt, Ignacy Chodźko and others) began in the late 1840s and early 1850s. Friendly relations and business ties were strengthened during the conditions of the liberalization of the regime under Governor-General Vladimir Nazimov (1855–1863). Key factors in the building the relations with Polish scientists and writers were their joint activities in the Vilnius Archaeological Commission and the post of censor, which was held by Kukolnik. He authorized the printing of books written by Władysław Syrokomla (Ludwik Kondratowicz), Antoni Edward Odyniec, Wincenty Korotyński, Karolina Proniewska and other Polish-speaking authors. Kukolnik held their works in high regard, especially espousing the religious motives that were close to him. In turn, Proniewska devoted a poem to him; at least seven Kukolnik’s poetic texts became the source of eight translations into Polish by Syrokomla, Korotyński, Odynieci (one poem was translated twice by Korotyński and Odyniec, one translation was published without a signature).
Keywords: Pavel Kukolnik, Lithuania, translation, Polish poetry, Russian poetry, literary connections